إدارة برنامج تعليم اللغة العربية في معهد "خلوة تحفيظ القرآن واللغة العربية" كارانج أنيار جاوى الوسطى - Ahyar Fauzan; Nuril Mufidah; Abdul Malik Karim Amrullah (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2022)
ملخص البحث: أصبحت إدارة برامج تعليم اللغة العربية بحاجة إلى الكثير من الدراسات من أجل تحسن جودتها، لأن إدارة برنامج التعليم الجيدة تزيد من دافعية الطلبة للتعلم. يهدف هذا البحث إلى وصف برنامج تعليم اللغة العربية في معهد "خلوة تحفيظ القرآن واللغة العربية" كارانج أنيار جاوى الوسطى، وصف إدارة البرنامج، وذكر المزايا والعيوب لهذه الإدارة. يستخدم هذا البحث المنهج الكيفي بنوع دراسة الحالة. ونتائج هذا البحث: (1) أن برنامج معهد خلوة هو برنامج تحفيظ القرآن وتعليم اللغة العربية بشكل مكثف خلال سنة واحدة. (2) إدارة هذا البرنامج يكون على أربع خطوات: التخطيط والتنظيم والتنفيذ والمراقبة. (3) مزايا إدارة برنامج الخلوة: البيئة اللغوية، ومبدأ المشاورة، ووحدة الفكرة والهدف، وإدارة الموارد البشرية، وعيوبها: قلة الخبرة، وقلة المدرسين، وعدم وحدة الأمر، والمنهج الدراسي ثقيل على الطلبة، وإشراف الطلبة، وإدارة الميزانية. الكلمات المفتاحية: إدارة تعليمية، تعليم اللغة العربية Abstract: The management of Arabic language education programs needs a lot of studies in order to improve its quality, because good education program management increases students' motivation to learn. This research aims to describe Arabic language teaching program at the “Kholwah Al Qur’an dan Bahasa Arab” Karanganyar Central Java, describe the management of the program, and mention the advantages and disadvantages of this administration. This research uses the qualitative approach with the type of case study. The results of this research: (1) The program of the “Kholwah Al Qur’an dan Bahasa Arab” is a program for memorizing the Qur’an and teaching the Arabic language intensively during one year. (2) The management of this program shall be in four steps: planning, organizing, actuating and controlling. (3) The advantages of managing the retreat program: the linguistic environment, the principle of consultation, the unity of idea and goal, and the management of human resources, and its disadvantages: lack of experience, lack of teachers, lack of unity of command, the curriculum is heavy on students, student supervision, and budget management. Keywords: Arabic teaching, educational management